In vitro test for inhibition of betel (Piper betle L.) and tembelekan (Lantana camara) extracts to anthracnose disease (Colletotrichum acutatum) in cayenne chili (Capsicum frutescens). Issue 2 (July 2021) - Khalifah, U; Amin, N; Junaid, M
Abstract: The continuous and excessive use of fungicides will disrupt the balance of the environment and is directly harmful to the health of consumers. The use of plants as botanical pesticides is an ecologically safe control method that has begun to be developed. The purpose of this study was to determine the effectiveness of betel and tembelekan extracts and the effect of the concentrations used in suppressing the growth of Colletotrichum acutatum fungi. Extraction was carried out using the maceration method, then the extract was concentrated using a rotary vaccum evaporator at a temperature of 40°C repeatedly until a concentrated solution was obtained. In the test of using treatments with several concentrations, that is K0:0%, K1:0.5%, K2:2%, K3:3.5% and K4:5%. Tests were carried out by growing C. acutatum mycelium on PDA media that had been mixed with plant extract solutions according to the treatment concentration. Colletotrichum acutatum mycelium was taken by cutting the PDA which was overgrown with a pure culture of C. acutatum with a media cutter using a cork borer. The results showed that the higher the concentration of the extract given would reduce the colony diameter of Colletotrichum acutatum and increase the percentage of inhibition. Betel extract at a concentration of 5% had the highest average percentage of inhibition compared to the tembelekan extract, namely 72.45%.